2023
DOI: 10.3390/f14020429
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Chionanthus retusus Seedlings to Drought and Waterlogging Stresses

Abstract: Understanding the adaptability of Chionanthus retusus Lindl. et Paxt. to extreme water conditions will help in exploring the potential application of this species in barren mountains. Three-year-old Chionanthus retusus seedlings were used in a greenhouse pot experiment that analyzed the effect of different moisture gradients on growth, photosynthetic and fluorescence characteristics, protective enzyme system, osmotic substance regulation and cell membrane damage. The results indicated that C. retusus can effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Liu et al [ 40 ] also discovered that water stress caused by changing precipitation patterns had negative effects on net photosynthetic rate, tree height, and basal diameter growth of black locust. The significant decline in gas exchange parameters was observed in many species under water stress [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 40 ] also discovered that water stress caused by changing precipitation patterns had negative effects on net photosynthetic rate, tree height, and basal diameter growth of black locust. The significant decline in gas exchange parameters was observed in many species under water stress [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chl fluorescence parameters are commonly used to describe the photosynthetic physiological conditions of plants, reflecting the degree of photosynthetic impact by stress (Bambach et al 2020, Niu et al 2023. Previous studies demonstrated that applying exogenous MT enhanced the photochemical efficiency of PSⅡ under Cd stress and protected PSⅡ from damage induced by chromium stress by controlling electron transfer flow (Ayyaz et al 2020, Zoufan et al 2023.…”
Section: Discussionmentioning
confidence: 99%